Global efforts in conquering lung cancer in China - Yan, Li (Chin J Cancer, 2015)
Lung cancer, the most prevalent and deadly malignancy in the world, poses a particularly critical healthcare challenge to China due to the rapidly increasing new cases and the unique cancer genetics in Chinese patient population. Substantial progress has been made in molecular diagnosis and personalized treatment of the disease. The field is now moving towards multiple new directions to include (1) new generation of targeted agents such as epidermal growth factor receptor and anaplastic lymphoma kinase inhibitors to overcome resistance to their early generation counterparts; and (2) deeper understanding of tumor genetics of each individual patient and consequently the application of biomarkers to guide personalized treatment as well as novel drug development including combination therapy. The increasing capacity in innovative cancer drug research and development is supported by extensive collaboration within China and globally, and across academia and industry, to build up expertise and infrastructure in early-phase clinical testing of novel drugs. With these combined efforts, new and better medicines will be available for lung cancer patients in China in the near future.